Sustainable Urban Development in Slum Areas in the City of Rio de Janeiro Based on LEED-ND Indicators - Ana Carolina Hyczy de Siqueira; Mohammad K. Najjar; Ahmed W. A. Hammad; Assed Haddad; Elaine Vazquez (Buildings, 2020)
The accelerated urban transition and its consequent unsustainability is a problem registered in several global scenarios. This issue has been identified in the city of Rio de Janeiro in Brazil. One of the solutions provided for this theme is the application of specific methodologies to measure sustainability in urban areas such as the case of Leadership in Energy and Environmental Design for Neighborhood Development (LEED-ND). This work aims to analyze a real urban project, still in the executive project phase, Morro do Encontro project, in the scenario of the slum area of Rio de Janeiro based on the LEED-ND indicator system. The novelty of this study is to evaluate the existing relationships, between urban development actions and sustainability, through LEED-ND indicators, in the proposals of the Brazilian government plan PAC2, as a means of verifying their effectiveness. A total of 12 boards of the discipline of Urbanism in the executive project phase are studied. The analyzed items are divided into credit items and mandatory items. A total of 8% of credit items (CI) and 33% of mandatory items (MI) are attended. The results found indicated 47 sustainability items were not met and, therefore, can be improved. This comes back to the fact that 100% of the mandatory LEED-ND items were not achieved, which means that this project as it was conceived cannot be considered as a sustainable urban solution.